Very Low-Dose Risperidone in First-Episode Psychosis: A Safe and Effective Way to Initiate Treatment. (9th January 2011) - McGorry, Patrick D.; Cocks, John; Power, Paddy; Burnett, Peter; Harrigan, Susy; Lambert, Tim
Abstract : Patients experiencing a first psychotic episode have high rates of extrapyramidal symptoms (EPSs) when treated with the doses of neuroleptics used in multiepisode or chronic schizophrenia. There is some evidence that lower doses may be equally, if not more, effective but less toxic in this population. Here, we report the results of a biphasic open label trial designed to assess the efficacy, safety, and tolerability of low-dose (2–4 mg/day) risperidone treatment in a group of 96 first-episode nonaffective psychosis patients. At the end of the trial, 62% of patients met the response criteria although approximately 80% had achieved a response at some time during the study. Reports of EPS remained low, and there were no dystonic reactions. We conclude that even at a dose of 2 mg/day, risperidone was highly effective in reducing acute symptomatology in a real world sample of young first-episode psychosis patients.